Exctraction of Foreign Body Aspiration in Children - Nisa Haska Maulina; Finny Fitry Yani (Institute of Computer Science (IOCS), 2021)
Aspiration of foreign bodies by children can lead to serious illness and sometimes even death. It commonly ocurs in children younger than 3 years old, as they tend to put objects in their mouth. A local epidemiology study also revealed that among paediatric patients suffering from this condition, 73% were below the age of 3 years. Bronchoscopy is an endoscopic technique of visualizing the inside of the airways for diagnostic and therapeutic purposes. This case reported a 1 years and 3 months old boy with foreign body aspiration. Bronchoscopy with rigid brochoscope was performed electively. Patient was clinically improved after the bronchoscopy.